« Fictif ou pas, c’est vrai ! » : l’usage de la fiction dans deux webdocumentaires consacrés au 17 octobre 1961 - Sophie Gebeil (Images du Travail, Travail des Images)
Broadcast online in 2011, the webdocumentaries "The Forgotten Night" (LNO) and "17.10.61" address, from various perspectives, the repression of 17 October 1961, one of the major events of the end of the Algerian war of independence in metropolitan France. This article focuses on the place of fiction within these two webdocumentaries in order to question the way in which web-native mediation formats produce a shift in the interference between fiction and reality, both in terms of the creative process and the perception that viewers have of it. In order to study how the web documentary transforms the fiction/documentary articulation, LNO and 17.10.61 are put into a historical perspective with regard to the dynamics specific to the diffusion of the event in the public space since 1961. In spite of distinct aesthetic and narrative choices, the two devices bear witness to the new documentary imaginary that is born from the crossroads between the tradition of historical documentary and digital culture.